ROLE-PLAY STRATEGY IN PRACTICUM CLASS FOR HOSPITALITY STUDENTS - Ida Bagus Manuaba (International Journal of Applied Science and Sustainable Development (IJASSD), 2020)
Practicum class plays an important role in vocational education which facilitating the gap between the two aspects; theoretical knowledge and practical skill. To accommodate the gap, Roleplay strategy is held in Practicum class. On the other hand, English is used as the main language in the class. Practical skill and communication skills for hospitality students can not be separated. English as a basic requirement for hotelier practitioners must be learned by students by combining the two aspects. Furthermore, students can be hesitant in doing an internship (On the Job Training) as a trainee or even as an employee in the hospitality industry (hotel, restaurant, cruise ship) because of their lack of Practical skill and communication skill. To overcome the problem, the role-playing strategy is applied in the practicum class. This study evaluates the effectiveness of role-play strategy in practicum class and the effect of implementing role play in the teaching process to the self-confidence of students in doing job training. This article concludes with a discussion of pedagogical implications and future research recommendations.